Survei Kepadatan Habitat Jentik Nyamuk Anopheles di Kampung Madong Kelurahan Kampung Bugis Tahun 2025 - Agus Dwi Cahya; Rinaldi Daswito; Risman Kurnia (Jurnal Kesehatan Lingkungan Mandiri, 2026)
Madong Village is a coastal area located in Kampung Bugis Subdistrict, characterized by swamps, lagoons, ponds, puddles, fishponds, and excavation sites that potentially serve as breeding places for Anopheles mosquitoes. Based on discussions with the Tanjungpinang City Health Office, several breeding habitats were identified as potentially positive for mosquito larvae. This study aimed to identify the density of habitats positive for Anopheles larvae in Madong Village. The research used a quantitative descriptive method with an observational survey design. The results showed that the distribution of breeding places formed curved, elongated, and separated patterns, consisting of both permanent and temporary habitats. The characteristics of these habitats included areas exposed and unexposed to direct sunlight, vegetation surrounding the habitats, and the presence of aquatic animals such as tilapia, snakehead fish, dragonfly larvae, and frogs. The average water pH ranged from 5.9–9.7, salinity was 0‰, and water temperature ranged from 29.1–34.7°C. All observed breeding places were negative for Anopheles larvae, resulting in a habitat index of 0%, indicating that the area is safe from malaria transmission by Anopheles mosquitoes. This study recommends that local health authorities conduct regular vector control and monitoring of potential mosquito breeding habitats to maintain environmental health and prevent malaria transmission.